Efektivitas Belanja Barang Dan Jasa Pada Kantor Kecamatan Tapa Kabupaten Bone Bolango - Umar, Reply Jusuf; Abdullah, Julie; Hasan, Wahyudin (Program Studi Akuntansi, 2023)
This study aims to determine and analyze the effectiveness of the budget for goods and services in the Tapa District Office, Bone Bolango Regency. This study uses the method of analysis of the effectiveness ratio. The data collection method used in this research is by means of documentation, interviews and observation.The results of this study indicate that the level or criteria for the effectiveness of the goods and services budget at the Tapa District Office, Bone Bolango Regency from 2018-2021 are classified as effective criteria. In 2018 the effectiveness rate was 97.22% (Effective). Then in the following year 2019, the level of effectiveness increased to 98.79% (Effective). Furthermore, 2020 is the year with the lowest level of effectiveness during the 2018-2021 period with an effectiveness rate of 93.31% but is still classified as Effective. Furthermore, 2021 will be the year with the highest level of effectiveness during the 2018-2021 period, namely 99.66% (Effective).